Implementasi Pembelajaran Al-Qur’an Tematik di Kuttab Ibnu Abbas Klaten - Sidiq Nugroho; Muhammad Munadi; Kusyaeni (Institut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2023)
This research aimed to explain the implementation of thematic al-Qur'an learning in Kuttab Ibnu Abbas Klaten. This research used a qualitative approach with a case study type. This research technique was carried out by observing, interviewing, and documenting, while the data analysis used analytical descriptive. The research results indicated that the implementation of thematic tahfizh al-Qur'an learning which was carried out in the early class Kuttab used the following steps: First, the initial activity of the teacher and students was to pray. Second, the core activities include: In this core activity, there were several activities carried out sequentially, namely (1) the teacher writes material on the blackboard, (2) students were asked to copy material in notebooks, (3) the teacher mentally recited verses to the students, (4) students memorized independently, (5) the teacher explained the meaning of letters, verses and key words. Third, the closing activity, in which the students repeated reading the verses they had memorized and the teacher asked questions about the meaning of the letter/verse.